WORK RELATED MUSCULOSKELETAL DISORDERS: A SURVEY OF PHYSIOTHERAPISTS IN TRICITY (International Journal of Physiotherapy, 2015)
Background: Musculoskeletal system disorders are common among health care workers worldwide. They are common causes of severe long-term pain and physical disability. Musculoskeletal disorders (MSDs) are defined as “regional impairments of the muscles, tendons, nerves and joints. Physiotherapy can lead to WRMSDs in physiotherapist because of the nature of their profession. Despite of having expert knowledge of musculoskeletal injuries and injury prevention strategies they still report a high incidence of work-related injuries during their professional practice due to their training and continuous professional developmentMethods: A total of 100 Physiotherapists which included 78 females and 22 males in the age group of 21 to 40 years were recruited in the study. The subjects were taken as per the inclusion and exclusion criteria from Tricity.Results: Pearson’s correlation and Chi square analysis was used to determine correlation and the association of prevalence of self-reported musculoskeletal symptoms with personal characteristics, job risk factors and coping strategies. The data obtained from this study documents that majority of Physiotherapists have experienced WRMSDs at some time. The prevalence of WRMSDs among Physiotherapists in Tricity is high (91%). The most common risk factors identified in the present study were dealing with an excessive number of patients in one day; continuing to work while injured or hurt; lifting or transferring dependent patients and work scheduling. In present study, the low back and neck regions were the most commonly affected site among physiotherapists (72.5%) each followed by upper back (28.6 %), shoulder (20.9%), wrist and hand (17.6%), knee (12.1%), ankle and foot (12.1%) and hip (7.70%)Conclusions: Work-related musculoskeletal disorders are an important health risk within the physiotherapy profession. The prevalence of work-related musculoskeletal disorders among the Physiotherapists in Tricity is high that is 91%. Hence, it supports the research hypothesis of the present study. It is also concluded that the low back and neck (72.5% each) are the most common sites susceptible to injury followed by upper back and shoulder